A study of the non-linear transport in single electron transistor at different temperature by using simon 2.0 - 508038 Nurul Syazana Aziz,ld1986-; Samsudi Sakrani, supervisor; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2008